Aneurysmal bone cyst of the frontal bone - Perić Predrag; Antić Branislav; Radić-Tasić Olga (Vojnosanitetski Pregled)
Background. Aneurysmal bone cyst (ABC) is a benign, expansive, osteolytic lesion that mainly occurs in young people, and involves the skull bones only exceptionally. The origin of ABC is controversial: secondary reactive bone lesion, or primary disease that represents an independent nosological entity. Blunt head trauma was suggested as a possible etiological factor. Case report. A case of a 19-year old man with primary ABC of the right frontal bone was reported. The lesion was totally excised through frontal craniotomy, and the skull bone defect primarily reconstructed with an acrilate cranioplasty. Five years after the surgery, the patient was without signs of local recurrence. Conclusion. Clinical and neuroradiological presentation of the skull ABC was not specific. Pathohistology confirmed the diagnosis. Total excision was the treatment of choice.